Semiempirical quantum mechanical method PM6-DH2X describes the geometry and energetics of CK2-inhibitor complexes involving halogen bonds well, while the empirical potential fails - Dobes, Petr; Rezác, Jan; Fanfrlík, Jindrich; Otyepka, Michal; Hobza, Pavel (The journal of physical chemistry. B, 2011)
In the present study, we have investigated complexes of CK2 protein kinase with halogenated inhibitors by means of the advanced semiempirical quantum mechanical (SQM) PM6 method (called PM6-DH2X), which describes various types of noncovalent interactions including halogen bonding well. The PM6-DH2X method provides reliable geometries of those CK2 protein kinase-inhibitor complexes involving halogen bonds that agree well with the X-ray crystal structures. When the Amber empirical potential is applied, this agreement becomes considerably worse. Similarly, the binding free energies determined by the PM6-DH2X SQM method are much closer to the experimental inhibition constants than those based on the Amber empirical potential.
Keywords: Models, Molecular; halogenace; Protein Binding; termodynamika; Protein Conformation; Casein Kinase II; molekulární modely; molekulární struktura; Molecular Structure; halogeny; Quantum Theory; Thermodynamics; Halogenation; kvantová teorie; vazba proteinů; kaseinkinasa II; Halogens; inhibitory enzymů; Enzyme Inhibitors; konformace proteinů